2004
DOI: 10.1590/s1516-635x2004000400009
|View full text |Cite
|
Sign up to set email alerts
|

Infectious bursal disease: evaluation of pathogenicity of commercial vaccines from Brazil in specific pathogen free chichens

Abstract: Infectious Bursal Disease (IBD) is a chicken disease economically important for the poultry industry in function of the immune depression that it causes. Disease control is made with different vaccines and vaccination programs. In present work, the pathogenicity of 3 intermediate vaccines (I1, I2 and I3), 2 intermediate more pathogenic (IP1 and IP2) and 3 vaccines containing strong virus (F1, F2 and F3) was evaluated. Birds vaccinated with IP1, IP2, F1, F2 and F3 showed significantly lower bursa size in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…The serological analyses also demonstrated that the intermediate vaccine induced a good production of anti-IBDV antibodies, which titers were similar to those obtained with the immunecomplex vaccine, which contains a "hotter"viral strain (2.995 and 2.921 log10, respectively). Studies have consistently reported the low pathogenicity of the intermediate vaccines in SPF chickens, and induction of antibody levels similar to those obtained with hot vaccines (Rautenschlein et al, 2003;Moraes et al, 2004;Padilha et al, 2005). However, it must be emphasized that commercially available intermediate vaccines may have different virulence degrees.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The serological analyses also demonstrated that the intermediate vaccine induced a good production of anti-IBDV antibodies, which titers were similar to those obtained with the immunecomplex vaccine, which contains a "hotter"viral strain (2.995 and 2.921 log10, respectively). Studies have consistently reported the low pathogenicity of the intermediate vaccines in SPF chickens, and induction of antibody levels similar to those obtained with hot vaccines (Rautenschlein et al, 2003;Moraes et al, 2004;Padilha et al, 2005). However, it must be emphasized that commercially available intermediate vaccines may have different virulence degrees.…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, Moraes et al (2004) recommends caution when using live vaccines that may cause BF lesions, as the recovery of bursal follicles may be only partial. Moreover, according to Iván et al (2001), the pathological effects caused by immune-complex vaccines are different on SPF birds compared with commercial birds with maternal immunity.…”
Section: Infectious Bursal Disease: Pathogenicity and Immunogenicity mentioning
confidence: 99%
“…When the scores are grouped in a binary fashion, simulating a more realistic situation where the animal is either healthy or sick, the ANN accuracy increases significantly. This is reinforced by Pereira (2002) and Moraes et al (2004) who suggest that a bird should be considered sick only when BF using optical score is 3 or more. Therefore regrouping the scores in a binary fashion for ANN training does make sense.…”
Section: Discussionmentioning
confidence: 93%
“…The bursa was scored according to the degree of lymphoid depletions as: score 1: 0-25%; score 2:26-50%; score 3: 51-80%; score 4: >81%.In addition, acute (edema, inter-follicular infiltration of inflammatory cells, follicular cysts, hyperemia) and chronic lesions (fibroplasia) of the bursa were determined according to Muskett et al (1979);Sterwart-Brown & Trampel (1990), and Moraes et al (2004).…”
Section: Histopathology Analysismentioning
confidence: 99%